Determinan Produk Domestik Bruto Sektor Pariwisata di Indonesia Tahun 1995-2024 - Febila Adinda Putri; Syaparuddin; Parmadi (PT. Saha Kreasi Indonesia, 2025)
This study aims to identify and analyze the development and the extent of the influence of the number of foreign tourist arrivals, average expenditure, average length of stay, and the Gross Domestic Product (GDP) of the tourism sector during the period 1995–2024. The research employs a quantitative approach using time series data obtained from the Central Bureau of Statistics (BPS) and the Ministry of Tourism and Creative Economy. The analytical method applied in this study is multiple linear regression analysis. The results show that during the research period of 1995–2024, the average growth of the tourism sector’s GDP in Indonesia was 13%, the number of foreign tourist arrivals increased by 193%, average expenditure by 3%, average length of stay by 2%, and foreign direct investment by 15%. The results of the multiple linear regression analysis indicate that the number of foreign tourist arrivals, average expenditure, and government policy have a significant effect, while the average length of stay has no significant effect on the tourism sector’s GDP in Indonesia during the period 1995–2024.